The Macroeconomics of Remittances : The Case of Tajikistan - Kireyev, Alexei (Washington, D.C. : International Monetary Fund, 2006)
The paper seeks to assess the macroeconomic implications of large-scale inward remittances for a small open economy. By including remittances in several standard models, the paper concludes that the overall macroeconomic impact of remittances is likely to be ambiguous. The impact depends on the structural characteristics of the receiving country, in particular its consumption and investment patterns, and its capacity to manage large financial inflows. As data deficiencies and methodological problems associated with remittances preclude crosscountry empirical investigation, the paper illustrates these findings with data on Tajikistan, where remittances as a share of GDP are among the highest in the world. The paper also evaluates the pros and cons of remittances in a broader political economy context.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet